2021
DOI: 10.1007/s10344-021-01545-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for recovery of large carnivores in humanized countries: attitudes and knowledge of sheep farmers towards brown bear in Western Pyrenees, Spain

Abstract: During 2017, we studied knowledge, perceptions, and attitudes towards brown bears by extensive mountain sheep farmers in the Western Pyrenees, using a structured questionnaire, specifically, whether the scarce bear presence, or the administrative region, was influential. Livestock raising practices are mainly family properties and have suffered a strong decline in the last decades. Despite its low abundance (only 2 bear individuals during the study period in the area), there was a generalized negative attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The main problems of extensive sheep farmers are not bear and wolf attacks on their herds, as happens in other situations [ 11 ]. The crisis of the system is due to other problems, which resulted in a decrease in the number of sheep and farms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main problems of extensive sheep farmers are not bear and wolf attacks on their herds, as happens in other situations [ 11 ]. The crisis of the system is due to other problems, which resulted in a decrease in the number of sheep and farms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with a prior study about the cultural images of snow leopards in Sanjiangyuan (Li et al, 2013) and other studies across the snow leopard range (Suryawanshi et al, 2013). In comparison, people held strong negative attitudes toward brown bears, a sentiment echoed in many other parts of the world (Herrero et al, 2021). This could be attributed to the fact that brown bears raid houses and injure humans, and consequently have a more profound impact on local communities than the other two species (Dai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the sample composition, the absence of bears and conflicts in the region for nearly 170 years and the social and cultural changes in rural areas since then may be behind this result (Ghasemi et al, 2021). Nevertheless, in such areas, attitudes can be very negative (Herrero et al, 2021) or become more negative after the bears return (Dressel et al, 2015). It can also be speculated that other factors, such as the awareness of the conservation status of the species and its declining population (Kaczensky et al, 2004), might explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…In the same area, García-de la Fuente et al (2010) found that more than 50% of the inquired population was willing to contribute to preserving the species. In the west Pyrenees, although the number of bears is extremely low, the attitude of farmers is very negative due to damage and incapacity to adapt husbandry (Herrero et al, 2021) but this is not generalized to all counties (Piédallu et al, 2016). In the Apennines, residents' attitudes toward bears are generally positive (Glikman et al, 2012), although dependent on perceived benefits related to the species (Glikman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%